Mathematical Critical Thinking Skills: Students' Analytical Ability on the Topic of Circles - Aziz, Saddam Al; Jupri, Al (International Journal of Geometry Research and Inventions in Education, 2025)
Critical thinking skills are one of the important competencies of the 21st century that need to be developed through mathematics learning, especially in flat geometry, namely circles. One important indicator of critical thinking is analytical skills, namely the ability to analyze information, identify relationships between concepts, and draw rational conclusions. This study aims to describe students' mathematical critical thinking skills in the indicator of analysis in circles. The research used a descriptive quantitative approach with a sample of 31 eighth-grade students at a public junior high school in Padang City. The instrument consisted of one essay question that asked students to analyze two different arguments related to the concepts of diameter and chord, choose the correct argument, and provide logical reasons based on the concept of circles. Scoring was done using an analytical rubric with a score range of 0–5. The results showed that only 3.22% of students were able to analyze correctly with logical reasoning, 6.45% of students could choose the correct argument but without a conceptual explanation, 80.65% of students were unable to analyze correctly and tended to copy the arguments in the questions, and 9.68% of students did not provide answers. These findings indicate that students' mathematical critical thinking skills, particularly their ability to analyze circle-related material, are still low. This study emphasizes the importance of mastering basic concepts as a foundation for promoting critical analysis skills in mathematical problem solving.